2007
DOI: 10.1007/s00299-006-0279-2
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation of photinia employing rhizobacteria to promote root development

Abstract: An alternative protocol was developed for in vitro propagation of photinia (Photinia x fraseri Dress), an ornamental shrub, using the plant growth-promoting rhizobacteria (PGPR) Azospirillum brasilense and Azotobacter chroococcum during rhizogenesis. Shoot tips from four-year-old mature plants, cut in spring and summer, were used as initial explants. They were cultured on Murashige-Skoog (MS) medium with Gamborg's vitamins, N(6)-benzyladenine (BA: 11.1 microM) and gibberellic acid (GA(3): 1.3 microM), obtainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 22 publications
3
28
0
4
Order By: Relevance
“…Like most woody plant species, photinia is reproduced by rooting apical cuttings with high concentration pulses of phytohormones (Bonaminio and Blazich 1983). This species is considered difficult to propagate by traditional cultural techniques, limiting their commercial utilization (Bonaminio and Blazich 1983;Ramírez-Malagón et al 1997;Larraburu et al 2007). Therefore, the use of in vitro culture techniques that allow mass production of cloned plants independent of time and season is recommended.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like most woody plant species, photinia is reproduced by rooting apical cuttings with high concentration pulses of phytohormones (Bonaminio and Blazich 1983). This species is considered difficult to propagate by traditional cultural techniques, limiting their commercial utilization (Bonaminio and Blazich 1983;Ramírez-Malagón et al 1997;Larraburu et al 2007). Therefore, the use of in vitro culture techniques that allow mass production of cloned plants independent of time and season is recommended.…”
Section: Introductionmentioning
confidence: 99%
“…Biotechnological techniques, such as the application of plant growth-promoting rhizobacteria (PGPR), have been effective in reducing the biochemical, anatomical and morphological modification of in vitro propagules in diverse species (Frommel et al 1991;Ait-Barka et al 2002;Nowak and Shulaev 2003;Larraburu et al 2007;Rodríguez-Romero et al 2008;Russo et al 2008). PGPR are a group of rhizosphere-colonizing bacteria that induce changes in inoculated plants, which can improve plant growth.…”
Section: Introductionmentioning
confidence: 99%
“…In their experiment, the inoculation was beneficial to some extent for Primula obconica but not for Rosa and Hydrangea quercifolia. The fully beneficial effect of bacterization of Robinia pseudoacacia with Rhizobium strains was observed by Balla et al (1998), and Photinia fraseri with Azospirillum brasiliense by Larraburu et al (2007). Zakharchenko et al (2010) reported better growth of potato and strawberry at acclimatization, when microshoots were inoculated before rooting with strain of Pseudomonas aureofaciens.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Larraburu et al (2007), bacterial inoculation was able to induce earlier rooting of photinia (Photinia  fraseri Dress) shoots. A. brasilense Cd with an indole-3-butyric acid pulse showed a significant increase in root fresh and dry weight, root surface area, and shoot fresh and dry weight, A. brasilense Sp7 enhanced root fresh weight and root surface area, but no significant differences were detected with A. chroococcum inoculation. )…”
Section: New Studies and Applications Of Pgprmentioning
confidence: 98%